PENGARUH PEMBELAJARAN BERDIFERENSIASI TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS III SDN DUKUH MENANGGAL I/424 MATERI PENGUKURAN PANJANG SATUAN BAKU - Dzulkifli, Alfi Rahmatita; Dian Kusmaharti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Education plays a crucial role in developing students' potential, improving their quality of life, and shaping their character in accordance with curriculum demands. In practice, there is still a mismatch between learning strategies and the diverse characteristics of students. Learning that equates student abilities results in low learning outcomes, particularly in mathematics. Therefore, a learning approach that accommodates differences in student abilities, interests, and learning styles is needed, one of which is through differentiated learning. This study aims to determine the effect of differentiated learning on mathematics learning outcomes and to assess student activity in the topic of length measurement using standard units in third-grade students at SDN Dukuh Menanggal I/424 Surabaya. This study used a quantitative approach with a Quasi-Experimental design and a Non-Equivalent Posttest Only Control Group Design. The subjects consisted of class III A as the experimental class, which received differentiated learning, and class III B as the control class, which used a scientific approach. Data collection techniques were conducted through tests and observations. The results showed that the data were normally distributed and homogeneous. Based on the Independent Sample T-Test, concluding that differentiated learning influenced students' mathematics learning outcomes. Furthermore, observations of student activity in differentiated learning yielded a total score of 56 out of 60, indicating that student activity was categorized as very active. Thus, differentiated learning has proven effective in improving learning outcomes and student engagement in mathematics learning on length measurement using standard units.